2004
DOI: 10.1021/ja037142o
|View full text |Cite
|
Sign up to set email alerts
|

Selective Interactions of Porphyrins with Semiconducting Single-Walled Carbon Nanotubes

Abstract: A derivatized porphyrin with long alkyl chains, 5,10,15,20-tetrakis(hexadecyloxyphenyl)-21H,23H-porphine, is selective toward semiconducting single-walled carbon nanotubes (SWNTs) in presumably noncovalent interactions, resulting in significantly enriched semiconducting SWNTs in the solubilized sample and predominantly metallic SWNTs in the residual solid sample according to Raman, near-IR absorption, and bulk conductivity characterizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
263
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(277 citation statements)
references
References 24 publications
10
263
0
4
Order By: Relevance
“…Maeda et al showed that m-SWCNTs could be highly concentrated to 87% by applying a dispersion-centrifugation process in a tetrahydrofuran solution of propylamine. 25 Similar results were also obtained in the m/s separation of SWCNTs by using bromine 26 and porphyrins 27 . The porphyrin and its derivates tend to attach onto the sidewalls of s-SWCNTs, making them enriched in the supernatant.…”
Section: Introductionsupporting
confidence: 78%
“…Maeda et al showed that m-SWCNTs could be highly concentrated to 87% by applying a dispersion-centrifugation process in a tetrahydrofuran solution of propylamine. 25 Similar results were also obtained in the m/s separation of SWCNTs by using bromine 26 and porphyrins 27 . The porphyrin and its derivates tend to attach onto the sidewalls of s-SWCNTs, making them enriched in the supernatant.…”
Section: Introductionsupporting
confidence: 78%
“…Pyrene and porphyrin are two of the most studied [13,14,15,16] functional groups highly interacting with CNTs. Therefore, the simplest concept to design our ideal dispersant would be to link one of these functional groups to a simple saturated alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…However, further improvements in both afforded yields and subsequently scaling-up processes are still needed. Postgrowth separation is an alternative technique that resulted in the enrichment of sc-SWNTs 13,14,17,18,20,21,28,29 . Despite their promises, each method still has its own limitations in scaling up and/or requires the tedious process of removing the insulating surfactants or polymers.…”
mentioning
confidence: 99%